The Iraqi countryside in a novel (Exceeded border): A study in the light of the critical approach - Jar-Allah, Ahmed Hussein (Al-Adab Journal, 2021)
The novel was generally distinguished from other literary arts in its connection with the living reality as an imaginative practice that relies on political, economic, social, intellectual and cultural references and as a crucial tool in reading cultural references and dive deep into reality. As every novelist has a vision to embody this reality. As every novelist has a vision to embody this reality. The novel of ("Exceeded border by Hammed Al-Kafa’i) is a considered a fertile field for presenting social issues in their apparent structure and revealing the cultural patterns behind them which lies in its deep structure. The novel here moves its characters in its imaginary world in a way that it becomes more capable of adaptation and crystallization of (cultural statements) that control the behaviour of characters, develop the narrative event and monitor personality transformations in rural society. The pattern of (class disparity) is dominates the joints of social life in the Iraqi countryside, as (AL-Saied) *4 enjoy those whose belongs by descent or race to the prophet Mohammed (Salaa Allah Ealayh Wasalam) *1 with enjoy special privileges not available to a (commoners) which reinforces the idea of class disparity in the Iraqi countryside. Within a male society in which the man imposed his control with strict provisions, the material and civil rights of women were lost and turned into a means and a tool to be to be exchanged according to the map of male interests, between a minor girl who is forced to marry under the saying (Kisma)*2 and another confiscates her freedom to choose her life partner and she is forced to marry her cousin under the saying (Al-Nahwa)*3 , and another is forcing her to stop her social life and cancel her feelings if her husband dies under the saying (loyalty to the husband after his death) and other sayings that tightened the noose on women in all their forms. On the level of religious belief, the novel is full of many signals that reveal the deep structure of the rural community that affects its behaviour, so it floats on the surface of the outward structure in the narrative context to describe some life practices as in the saying (intercession) that explains many behavioural practices that seem ambiguous in relation to the other, those who are outside the Shiite sect or belief as well as the say (Divine Punishment) by which some behaviours are interpreted according to religious beliefs, in addition to the special immunity granted to the (AL-Saied) this culture, which prevails, represents the first line of defence that puts them under protection from anything. The saying (Al-Barakah) *5 comes to give them some privileges that guarantee them to stay at the top of the social ladder. *1 (Salaa Allah Ealayh Wasalam): Means Blessings and peace be upon the Prophet Muhammad. *2Kisma: It means that some Arab societies force the girl to marry under certain customs called Kisma. *3Al-Nahwa: means that the girl is forced to marry a cousin under certain norms called Al-Nahwa. *4Al-Sayed: It is believed that his lineage belongs to the Prophet Muhammad, peace and blessings be upon him. *5Al-Barakah: it means granting gentlemen a blessing to people some privileges that put them on top of the social ladder.